Coping with crowding: The prison system response to the crowding crisis - McCarthy, Bernard J. (American journal of criminal justice, 1989)
The prison crowding problem in the United States has been described by the Department of Justice as one of the most critical problems facing the criminal justice system (Gettinger, 1984). During the past several years numerous state and federal, public and private task forces and advisory groups have proposed solutions to the crisis but, as of yet, the proposals advanced by criminal justice policy analysts have done little to ease the crowding crisis. In light of the failure of various planning groups to deal with the problem of crowding, this paper examines how the correctional systems have coped with prison crowding through the use of shortterm ad hoc solutions during the 1980s.